Large-Scale Geographic Size Variability of Cyprideis torosa (Ostracoda) and Its Taxonomic and Ecologic Implications - Wrozyna, Claudia; Mischke, Steffen; Hoehle, Marlene; Gross, Martin; Piller, Werner E. (Frontiers in Ecology and Evolution, 2022)
Body-size variability results from a variety of extrinsic and intrinsic factors (environmental and biological influences) underpinned by phylogeny. In ostracodes it is assumed that body size is predominantly controlled by ecological conditions, but investigations have mostly focused on local or regional study areas. In this study, we investigate the geographical size variability (length, height and width) of Holocene and Recent valves of the salinity-tolerant ostracode species Cyprideis torosa within a large geographical area (31° - 51° latitude, and 12° - 96° longitude). It is shown that distant local size clusters of Cyprideis torosa are framed within two large-scale geographical patterns. One pattern describes the separation of two different size classes (i.e., morphotypes) at around ~42° N. The co-occurrence of both size morphotypes in the same habitats excludes an environmental control on the distribution of the morphotypes but rather could point to the existence of two differentiated lineages. Generally, correlations between valve size and environmental parameters (salinity, geographical positions) strongly depend on the taxonomic resolution. While latitude explains the overall size variability of C. torosa sensu lato (i.e., undifferentiated for morphotypes), salinity-size correlations are restricted to the morphotype scale. Another large-scale pattern represents a continuous increase in valve size of C. torosa with latitude according to the macroecological pattern referred as Bergmann trend. Existing explanations for Bergmann trends insufficiently clarify the size-cline of C. torosa which might be because these models are restricted to intraspecific levels. The observed size-latitude relationship of C. torosa may, therefore, result from interspecific divergence (i.e., size-ordered spatial sorting) while environmental influence is of minor importance. Our results imply that geographical body-size patterns of ostracodes are not straightforward and are probably not caused by universal mechanisms. Consideration of phylogenetic relationships of ostracodes is therefore necessary before attempting to identify the role of environmental controls on body size variability.